Human Parechovirus Infection in Neonates and Children: An Overview - Shee, Anutosh; Weber, Heinrich (Journal of Pediatric Infectious Diseases, 2017)
Pediatricians are becoming increasingly aware of the emergence of human parechovirus (HPeV) following several reports of potentially life-threatening infection in early infancy across the globe from Europe to Australia with episodic seasonal outbreaks. The severity of the HPeV infection varies widely from sporadic mild respiratory or gastrointestinal tract infection in older children to epidemic severe sepsis, myocarditis, and meningoencephalitis in young infants up to 3 months of age. Early complete recovery may sometimes be falsely reassuring, which later can lead to poor neurodevelopmental outcomes. The underlying causative viral agent of meningoencephalitis may remain elusive if a specific laboratory test for HPeV is not requested. Unlike Enterovirus (EV), cerebrospinal fluid (CSF) analysis in HPeV infection may remain misleadingly normal without pleocytosis or abnormal glucose and protein values even in PCR-positive cases. In this review article we attempt to summarize the important clinical information relevant to the practicing pediatricians about HPeV, particularly about its most pathogenic type, HPeV genotype 3 (HPeV3) along with its complications, possible treatment options, and future research direction.
Keywords: human parechovirus; Enterovirus; intravenous immunoglobulin; neutralizing antibody titers; meningoencephalitis